Heterocycles and a Sorbicillinoid from the Coral-Derived Fungus Penicillium chrysogenum - Junjie Yang; Yuan Zong; Cili Wang; Kai Li; Yue Zhang; Pinglin Li (Marine Drugs)
A detailed chemical study of the culture of a coral-derived fungus Penicillium chrysogenum resulted in the isolation and identification of four new aromatic heterocycles chrysoquinazolinones A–B (1–2) and chrysobenzothiazoles A–B (3–4), along with a new sorbicillinoid 4-carboxylsorbicillin (5). Chrysoquinazolinones A–B (1–2) combine a quinazolinone fragment with a bicyclo[2.2.2]octane or a pyrrolidone moiety, respectively, demonstrating the unexpected structures of marine natural products. Chrysobenzothiazoles A–B (3–4) possess a benzothiazole system and are the second isolation of this class of skeleton compounds from marine organisms. The existence of the pair of enantiomers (±3) was deduced by chiral HPLC analysis. Their structures and absolute configurations were elucidated by detailed spectroscopic analysis, comparison with the literature data, single-crystal X-ray crystallographic analysis and TDDFT-ECD calculations. Compound 5 exhibited moderate cytotoxicity against K562 and NCI-H446 cell lines, with IC50 values of 15.00 μM and 16.87 μM, respectively.